Stainless steel top-seat angle beam-to-column connection: Full-scale test and analytical modelling. (December 2021) - Hasan, Mohammad Jobaer; Ashraf, Mahmud; Al-Deen, Safat; Shill, Sukanta Kumer; Uy, Brian
Abstract: Stainless steel (SS) is increasingly used for structural applications in the construction industry as its beneficial properties outweigh initial material costs when sustainability aspects and the whole life cycle of structures are appropriately accounted for in the structural design. Despite the well-recognised significance of connections in bare metallic construction, experimental research on SS beam-to-column connections, especially full-scale test results, are scarce. This paper presents a full-scale experimental investigation on the semi-rigid behaviour of top-seat bolted connection (also known as 'flange cleat' connection) made from austenitic SS. Deformation characteristics of various elements of the connection were carefully investigated and subsequently used to calibrate nonlinear FE models for parametric analysis. Obtained numerical results were used to develop a four-parameter power model that relies on simplified expressions for key input parameters to predict the semi-rigid behaviour of bolted top-seat connections. Results predicted using the proposed model and those obtained using currently available techniques based on carbon steel behaviour were compared. Outcomes of the current research highlighted the significance of appropriate inclusion of stain hardening offered by austenitic grade to capture the semi-rigid response of such connections.